Demokrasi di Indonesia dalam Realitas Politik di Papua: Refleksi Mahasiswa dalam Perjuangan Hak Adat - Kegiye, Silpius (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to (1) compare the concept of ideal democracy in Indonesia with its implementation in Papua; (2) analyze how the struggle of Papuan communities to obtain recognition of customary (indigenous) rights is perceived and addressed within the autonomy system; and (3) explore the reflections, roles, and advocacy strategies of Papuan students in pursuing the recognition and protection of customary rights. This research employs a qualitative method with a literature-based approach. The collected data are analyzed qualitatively. The results indicate that, based on findings related to democracy, conditions in Papua, and students’ perspectives, democracy in Indonesia—largely characterized by a hybrid model and facing challenges in strengthening its system—provides a backdrop for students to compare various forms of democracy. Students recognize that democratic processes do not always progress linearly and may regress to less free conditions. This political reality shapes Papuan and pro-Papuan students’ perspectives to be highly critical, fact-oriented, and demanding clear explanations. In the Papuan context, political realities marked by failures in Special Autonomy, domination by power elites, and ongoing debates between development and indigenous land rights have reinforced students’ belief that the democratic model applied in Indonesia has failed to create social justice or recognize the dignity of Indigenous Papuans. The failure of the Papuan People’s Assembly (MRP) to safeguard and protect customary rights further strengthens the view that unequal governance mechanisms are used by the government primarily to maintain control rather than to promote public welfare.